IMPROVING FRACTION OPERATION SKILLS OF MULTIPLICATION AND DIVISION THROUGH THE APPLICATION OF DOMINO CARD TO STUDENT OF GRADE V SDN 02 PULOSARI ACADEMIC YEAR 2017/2018. - Retnowati, Rohmatul Putri; Kamsiyati, Siti; Matsuri, Matsuri (Universitas Sebelas Maret, 2018)
This research is focusing about using domino card as media that improve the skills of multiplication counting operations and fractional division in the students of class V SDN 02 Pulosari academic year 2017/2018.The objectives of this research is to improve the skills of multiplication counting and fractional division by applying the domino card media to the students of class V SDN 02 Pulosari academic year 2017/2018.This research method is Classroom Action Research with two cycles. Every consists of planning, execution, action, observation and reflection. Subjects in this study were students of grade 5th SDN 02 Pulosari which consisting 25 students. The data sources are primary data sources and secondary data sources. Data analysis technique is comparative descriptive analysis technique.The study produce an average of thevalue of pra sycle skills action fraction is 61,1 with completeness 28%. First sycle is 71,9 as reference for classical completeness with 44% source data and the average value of fractional counting operation skills of second sycle is 81.9 with a percentage of mastery of 80%. Based on the results of this study can be concluded that the use of domino card media can improve the skills of multiply counting operations and fractional divisions in students of class V SDN 02 Pulosari.